Socioeconomic profile of the elderly in Florianópolis: Comparative analysis studies Perfil do Idoso 2002 and EpiFloripa Idoso 2009 - Danielle Ledur Antes; Daniela Furuzawa Ribeiro; Ione Jayce Ceola Schneider; Tânia Rosane Bertoldo Benedetti; Eleonora d'Orsi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: The aim of this study is to compare the socioeconomic profile of the population aged 60 or older living in Florianópolis in 2002 and 2009. METHODS: Data were obtained through the studies Perfil do Idoso 2002 and EpiFloripa Idoso 2009 based on household surveys. RESULTS: There was a predominance of aged 60 to 69 years old, married and living with spouse and children. There was a significant improvement in the level of education and, on the economic aspects, retirement remains the main source of income, increasing the number of families receiving no more than three minimum wages and reducing those with monthly income above 10 minimum wages. The number of older adults who considers their current financial situation better than age 50 increased as the proportion of subjects with fair/poor self-perception health. It was also highlighted greater purchasing private health insurance. CONCLUSION: Comparison of the two studies presented here can support the actions of managers in order to bring effective results to the population.